Therapeutic Potency of the “Holy Mud and Water” in Selected African Initiated Churches in Rivers State, Nigeria - Mpigi, Goka Muele; Bob-Manuel, Lolo Friday (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025, 2025)
Western biomedicine is an explicit method to therapeutic illnesses with evidence-based treatment validated through biological research, with treatment administered via formally trained doctors, nurses, and other such licensed medical practitioners. In contrast, the African Initiated churches (AICs) see the therapeutic efficacy in restoring health in nature. Unfortunately, there were several attempts in the form of crusades to eliminate any ‘primeval knowledge’, and spirituality by the scientifically, economically and socially dominant western powers. Despite its significance, little research exists on the therapeutic efficacy of holy water in AICs. And besides the wide application of the sacred elements of mud and water, the therapeutic potency of it, remains poorly understood, leading to scepticism and mistrust. This knowledge gap necessitates an in-depth examination of holy water's role in AICs. This paper therefore is an attempt to show the therapeutic potency of the holy mud and water adopted as found in some African initiated churches in Rivers State, Nigeria for healing processes. The paper adopts the local content policy of Nigeria which was specifically designed to build domestic capacity relevant for service and product delivery; and encourage increase participation of local and indigenous institutions, ideas, knowledge and heritage for human socio-spiritual wellbeing as the theoretical tool to validate this research claims. A qualitative and descriptive method blended with ethnographic approach was employed to investigate the therapeutic potency of holy mud and water in three selected AICs. This study draws on symbolic interactionism as the theoretical frame and analytical mill. The results indicate that holy mud and water is perceived as a multifaceted healing agent, addressing spiritual, psychological, and physical ailments. Findings reveal that naturopathic (alternative) medicine such as the "Holy mud and water" are local wisdom and potent natural and spiritual objects for healing and wellbeing and recommends that indigenous knowledge such as this should be encouraged and harnessed as it is cost effective accessible and easily available. Paper further recommends an integration of traditional healing practices into mainstream healthcare. There should be enhanced collaboration between the AICs and healthcare providers and conduct further research on the therapeutic potency of holy mud and water in Nigeria. Keywords: Healing, Ritual, Therapeutic, Holy Mud and Water